Effect of Span 20 Feeding Zone in the Twin Screw Extruder on the Properties of Amorphous Solid Dispersion of Ritonavir - Hengqian Wu; Zhengping Wang; Yanna Zhao; Yan Gao; Heng Zhang; Lili Wang; Zhe Wang; Jun Han (MDPI AG, 2023)
A ternary amorphous solid dispersion (ASD) system consisting of drug/polymer/surfactant is receiving increased attention to improve the oral bioavailability of poorly water-soluble drugs. The effect of polymers has been extensively studied, while the impact of surfactants has not yet to be studied to the same extent. Challenging questions to be answered are whether the surfactants should be added with the drug or separately and the resulting differences between the two operating processes. By adjusting the liquid feeding zone for Span 20 in the hot-melt twin screw extruder equipment, we investigated the effect of Span 20 on the properties of the polyvinylpyrrolidone/vinyl acetate (PVPVA)-based ASD formulations of ritonavir. We found that with the delayed feeding positions of Span 20 in the twin screw extruder, the ability of the ternary ASDs to maintain the supersaturation of the milled extrudates was observed to be significantly enhanced. Furthermore, adding surfactant after a thorough mixing of polymer and drug could decrease the molecular mobility of ternary ASD formulations. In addition, the effects of Span 20 on the complex viscosity and structure of PVPVA were also investigated. The delayed addition of Span 20 could improve the complex viscosity of PVPVA, thus leading to the drug precipitation inhibition. In conclusion, the delayed addition of Span 20 in the twin screw extruder and prolonging the mixing time of the drug and polymer may be critical to the maintenance of supersaturation.